A revolving door: A qualitative investigation of release from professional baseball - Raabe, J.; Zakrajsek, R. A.; Bass, A. D.; Readdy, T. (International Journal of Sport and Exercise Psychology, 2018)
Athletes endure multiple transition phases over the course of their career (both in and out of sport). The context of professional baseball offers the potential to gain a unique perspective on the experience of forced transition out of sport (i.e. being released). Every year approximately 1500 individuals will be released from professional baseball and close to 90% of all athletes will likely be released at some point in their career, creating a "revolving door" in Minor League Baseball (MiLB). Semi-structured interviews were conducted with 12 former MiLB players to understand the experience of being released from professional baseball and identify coping strategies applied during the forced transition. Analysis of the qualitative data revealed two domains: (a) aspects that influenced processing of the release and (b) factors that facilitated a successful transition out of baseball. The findings highlighted positive appraisals and coping strategies that former MiLB players had used to enhance their transition out of sport. Having a back-up plan, utilising connections, and maturing through college experiences alleviated some of the challenges participants faced and helped them to be better prepared for an exit from the revolving door that is MiLB and enter a new phase of their professional life. In sum, the current research helped gain a better understanding of release from professional baseball and provided information that can help to assist athletes who are going through this experience.